2019
DOI: 10.2147/idr.s196800
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characterization of the most common <em>embCAB</em> gene mutations associated with ethambutol resistance in <em>Mycobacterium tuberculosis</em> isolates from Iran</p>

Abstract: IntroductionEthambutol (Emb) is one of the first-line drugs in the standard combination therapy for tuberculosis; however, due to the rapid increase in Emb resistance among clinical isolates of Mycobacterium tuberculosis (MTB), early detection of Emb resistance is desirable. As the embCAB operon is considered involved in resistance to Emb, this study aimed to analyze the most common mutations within the embCAB operon among MTB isolates from Iran to find any correlations of these mutations with Emb resistance.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…Ethambutol resistance was mostly linked to the mutations within the embB gene (codon 306 as the dominant position), but not embA. Khosravi et al reported embA mutation from EMB-susceptible strains [47]. Additionally, Sun et al revealed that 82.6% of EMB-resistant isolates from China had at least a mutation in the embABC locus, but contrary to this study, they were located mostly in the embA and embB upstream region [48].…”
Section: Discussioncontrasting
confidence: 71%
“…Ethambutol resistance was mostly linked to the mutations within the embB gene (codon 306 as the dominant position), but not embA. Khosravi et al reported embA mutation from EMB-susceptible strains [47]. Additionally, Sun et al revealed that 82.6% of EMB-resistant isolates from China had at least a mutation in the embABC locus, but contrary to this study, they were located mostly in the embA and embB upstream region [48].…”
Section: Discussioncontrasting
confidence: 71%
“…In order to find new possible resistance-related mutations, we further analyzed all mutations in genes above and another 15 resistance-related genes for INH ( nat, ndh, iniA, iniB , and iniC ), PZA ( rpsA and panD ), EMB ( embC, embR , and ubiA ), SM ( gidB ), and CLO resistance ( rv1979c, rv2535c, mmpL3 , and mmpL5 ) (Table S1) (Wong et al, 2011; Zhang et al, 2013, 2015a; Hartkoorn et al, 2014; Shi et al, 2014; Vilchèze and Jacobs, 2014; Almeida et al, 2016; Li et al, 2017; Ismail et al, 2018; Sun et al, 2018; Khosravi et al, 2019; Tulyaprawat et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…PCR showed that the mutation rate in 10 EMB-resistant TB strains was 20% (10% mutation in embB codon 306 Met–Val and 10% in embC codon 270 Thr–Ile). [ 59 ] According to other research studies in Iran that were performed in 2015, the prevalence of TB was 66.4%, among which 7% had extrapulmonary TB. [ 60 ] Efficiency of the Bacillus Calmette-Guerin (BCG) vaccine has been proved, but the type, dose, and strength of the vaccine strain, age, and inoculation technique are different and cause Mendelian susceptibility to mycobacterial disease (MSMD) primary immunodeficiency (PID).…”
Section: Discussionmentioning
confidence: 99%